Abdominal Aortic Endothelial Dysfunction Occurs in Female Mice With Dextran Sodium Sulfate-Induced Chronic Colitis Independently of Reactive Oxygen Species Formation - Wu, Hao; Hu, Tingzi; Zhang, Linfang; Xia, Xiujuan; Liu, Xuanyou; Zhu, Qiang; Wang, Meifang; Sun, Zhe; Hao, Hong; Cui, Yuqi; Parrish, Alan R.; Li, De-Pei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background and Objective Inflammatory bowel disease (IBD) produces significant local and systemic inflammation with increased reactive oxygen species (ROS) formation. IBD Patients are at an increased risk for developing endothelial dysfunction and cardiovascular diseases. The present study tested the hypothesis that IBD impairs aortic endothelial function via ROS formation and investigate potential sex-related differences. Methods and Results Acute and chronic colitis models were induced in male and female C57BL/6 mice with dextran sodium sulfate (DSS) treatment. Aortic wall stiffness, endothelial function, and ROS levels, as well as serum levels of pro-inflammatory cytokines were evaluated. Acetylcholine (Ach)-induced endothelium-dependent relaxation of abdominal aorta without perivascular adipose tissue (PVAT) was significantly reduced in female mice, not males, with chronic colitis without a change in nitroglycerin-induced endothelium-independent relaxation. PVAT effectively preserved Ach-induced relaxation in abdominal aorta of female mice with chronic colitis. Aortic peak velocity, maximal intraluminal diameters, pulse wave velocity, distensibility and radial strain were preserved in mice with both acute and chronic colitis. Although pro-inflammatory cytokines levels were increased in mice with acute and chronic colitis, aortic ROS levels were not increased. Conclusion The data demonstrate that abdominal aortic endothelial function was attenuated selectively in female mice with chronic colitis independent of ROS formation. Further, PVAT played an important role in preserving endothelial function in female mice with chronic colitis.